2016
DOI: 10.1111/jam.13327
|View full text |Cite
|
Sign up to set email alerts
|

A future perspective on neurodegenerative diseases: nasopharyngeal and gut microbiota

Abstract: Summary Neurodegenerative diseases are considered a serious life‐threatening issue regardless of age. Resulting nerve damage progressively affects important activities, such as movement, coordination, balance, breathing, speech and the functioning of vital organs. Reports on the subject have concluded that neurodegenerative disease can be caused by mutations of susceptible genes, alcohol consumption, toxins, chemicals and other unknown environmental factors. Although several diagnostic techniques can be used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 167 publications
(251 reference statements)
0
7
0
2
Order By: Relevance
“…Approximately 60% of the bacterial genera present in our intestine form spores which likely facilitates their host-to-host transmission [26]. Furthermore,three rapid PCR-based methods, the terminal-restriction fragment length polymorphism (T-RFLP) [27] and the temperature/denaturing gradient gel electrophoresis (DGGE/TGGE) [28,29] are used to generate a fingerprint of an unknown microbial community to provide a good basis for comparing communities, however these methods are now largely replaced by high throughput sequencing above mentioned [30]. Finally, flow cytometry has long been appreciated as a technology that delivers multi-parametric information on the single cell level at a high throughput and with the opportunity for physical separation of cells (FACS sorting).…”
Section: Technological Advances To Investigate the Gut Microbiota Andmentioning
confidence: 99%
“…Approximately 60% of the bacterial genera present in our intestine form spores which likely facilitates their host-to-host transmission [26]. Furthermore,three rapid PCR-based methods, the terminal-restriction fragment length polymorphism (T-RFLP) [27] and the temperature/denaturing gradient gel electrophoresis (DGGE/TGGE) [28,29] are used to generate a fingerprint of an unknown microbial community to provide a good basis for comparing communities, however these methods are now largely replaced by high throughput sequencing above mentioned [30]. Finally, flow cytometry has long been appreciated as a technology that delivers multi-parametric information on the single cell level at a high throughput and with the opportunity for physical separation of cells (FACS sorting).…”
Section: Technological Advances To Investigate the Gut Microbiota Andmentioning
confidence: 99%
“…The link between PD and nasal microbiota has been examined. The results indicated that the dysbiosis of the nasopharyngeal microbiota creates the inflammatory response to α-synuclein that ends in neurodegenerative disorders [ 140 , 141 ]. The accumulation and aggregation of α-synuclein in the dopaminergic substantia nigra of the CNS cause a neuronal loss in PD [ 142 ].…”
Section: Olfactory Dysfunction and Neurological Disordersmentioning
confidence: 99%
“…Дистанционные взаимодействия поддерживаются за счет обмена метаболитами (сигнальными молекулами микробиотического происхождения) [39,40]. ГАМК -антистрессорный медиатор, продуцируется в больших количествах бактериальной микрофлорой, особенно бифидобактериями, образует единый пул с эндогенной фракцией ГАМК и непосредственно воздействует на нервные окончания в ЖКТ, стимулируя также эпителиальные клетки кишечника, которые высвобождают молекулы, модулирующие нейропередачу в энтеральной нервной системе, оказывая влияние на мозг и поведение макроорганизма [41][42][43][44].…”
Section: регуля торные метаболиты симбиотических бактерийunclassified